2017
DOI: 10.4081/ijfs.2017.6501
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondii and pre-treatment protocols for polymerase chain reaction analysis of milk samples: a field trial in sheep from Southern Italy

Abstract: Toxoplasmosis is a zoonotic disease caused by the protozoan Toxoplasma gondii. Ingestion of raw milk has been suggested as a risk for transmission to humans. Here the authors evaluated pre-treatment protocols for DNA extraction on T. gondii tachyzoite-spiked sheep milk with the aim of identifying the method that resulted in the most rapid and reliable polymerase chain reaction (PCR) positivity. This protocol was then used to analyse milk samples from sheep of three different farms in Southern Italy, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 16 publications
1
14
0
Order By: Relevance
“…Many different molecular techniques are used for diagnosis of T. gondii in milk samples as conventional PCR [ 18 , 19 ], nested PCR [ 23 ], PCR-RFLP technique [ 24 ], and qPCR [ 25 , 26 ]. qPCR assay is the most rapid, accurate, and effective molecular technique that can be used for Toxoplasma detection [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many different molecular techniques are used for diagnosis of T. gondii in milk samples as conventional PCR [ 18 , 19 ], nested PCR [ 23 ], PCR-RFLP technique [ 24 ], and qPCR [ 25 , 26 ]. qPCR assay is the most rapid, accurate, and effective molecular technique that can be used for Toxoplasma detection [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The main detection methods used on raw milk samples involve the detection of T. gondii DNA using PCR‐based tests, most commonly targeting the 529 bp repeat element (Bezerra et al., ; de Santana Rocha et al., ; da Silva et al., ; Vismarra et al., ) or the B1 gene (Dehkordi et al., ).…”
Section: Assessmentmentioning
confidence: 99%
“…T. gondii has been detected in raw milk from infected animals using a variety of techniques, mainly using PCR, tissue culture, and in vivo bioassays (Dehkordi et al., ). A recent study sampled 21 milk samples taken from three different sheep farms in southern Italy and found one milk sample to be positive using a PCR assay (Vismarra et al., ). A previous study in Italy looking at goat milk found 13% of 77 samples to be positive using a T. gondii ‐specific PCR test (Mancianti et al., ).…”
Section: Assessmentmentioning
confidence: 99%
“…The presence of T. gondii DNA in camel milk has been reported in several studies [ 38 , 39 , 54 ], even though in another study all specimens tested negative [ 53 ]. The literature dealing with potential infection of ovine milk has been recently reviewed [ 57 ], and T. gondii DNA and viable tachyzoites occurrence has also been reported [ 38 , 39 , 48 , 53 , 54 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ]. Camossi et al [ 59 ] reported the presence of T. gondii DNA in milk from naturally infected ewes and detected T. gondii DNA twice in the milk of two sheep, suggesting a possible resurgence of tachyzoites from cysts, which can circulate again and be excreted through the milk.…”
Section: Discussionmentioning
confidence: 99%